Peri-ultrasound modeling for surface wave propagation - Hafezi, Mohammad Hadi; Kundu, Tribikram (Ultrasonics, 2018)
•Peri-ultrasound modeling tool is used to model surface wave propagation.•Both linear and non-linear ultrasonic behaviors are successfully modeled.•Numerical results are compared with both analytical and experimental results in absence and presence of a crack, respectively.•A crack’s effect on the retrograde elliptic motion of the surface particle is investigated. The interaction between surface wave and a surface breaking crack is studied using a novel fast modeling tool called peri-ultrasound that can model both linear and nonlinear ultrasonic response. This modeling approach is based on peridynamic theory. In this study, the surface wave is modeled by applying a triangular pulse excitation function on the surface of a large structure. The particle movements are simulated on both sides of the surface crack to investigate transmitted and reflected fields. This investigation shows that: (1) the computed amplitude spectra of the Rayleigh wave agrees with the experimental observation; and (2) the structure containing a surface breaking crack shows noticeable increase in its nonlinear behavior. The computed results have been also verified against the analytical solution for a half-plane problem made of homogenous, isotropic, linear elastic material (Lamb’s Problem).